Use of noninvasive ventilation in immunocompromised patients with acute respiratory failure: a systematic review and meta-analysis. Issue 1 (December 2017) - Huang, Hui-Bin; Xu, Biao; Liu, Guang-Yun; Lin, Jian-Dong; Du, Bin
Abstract Background Acute respiratory failure (ARF) remains a common hazardous complication in immunocompromised patients and is associated with increased mortality rates when endotracheal intubation is needed. We aimed to evaluate the effect of early noninvasive ventilation (NIV) compared with oxygen therapy alone in this patient population. Methods We searched for relevant studies in MEDLINE, EMBASE, and the Cochrane database up to 25 July 2016. Randomized controlled trials (RCTs) were included if they reported data on any of the predefined outcomes in immunocompromised patients managed with NIV or oxygen therapy alone. Results were expressed as risk ratio (RR) and mean difference (MD) with accompanying 95% confidence interval (CI). Results Five RCTs with 592 patients were included. Early NIV significantly reduced short-term mortality (RR 0.62, 95% CI 0.40 to 0.97, p  = 0.04) and intubation rate (RR 0.52, 95% CI 0.32 to 0.85, p  = 0.01) when compared with oxygen therapy alone, with significant heterogeneity in these two outcomes between the pooled studies. In addition, early NIV was associated with a shorter length of ICU stay (MD −1.71 days, 95% CI −2.98 to 1.44, p  = 0.008) but not long-term mortality (RR 0.92, 95% CI 0.74 to 1.15, p  = 0.46). Conclusions The limited evidence indicates that early use of NIV could reduce short-term mortality in selected immunocompromised patients with ARF. Further studies are needed to identify in which selected patients NIV could be more beneficial, before wider application of this ventilator strategy.